OS IMPACTOS DA FORMAÇÃO CONTINUADA DE PROFESSORES DE UMA ESCOLA DO CAMPO - Farias, Maria Goretti Rocha (2018)
This research is the result of studies carried out at the Master’s degree course in the Teaching of Humanities and languages at the Universidade Franciscana. The research aimed at understanding the impacts of continued formation in the teachers’ professional development in final years at the Escola Municipal de Ensino Fundamental José Paim de Oliveira in Santa Maria-RS. Methodology comprised the qualitative approach of case study type. Six teachers of the final years at the referred school took part in the research. Interviews were accomplished as the data collecting tool with guided topics to direct them. The resource of documental analysis was also used and it was vital for getting information related to the research field as well as knowing and analyzing the political-pedagogical projects and the school pedagogical projects. Content analysis was the technic for data analysis (Bardin; 2006). Results highlight that the continued building up of the rural education teachers must have as its premise to consider the cultural environment and the knowledge built from those community subject’s life experience. For that, it is necessary to base teachers’ building up on those principles. This way rethinking this formation model is really important, in order to take care of the specificities of different context in school education. Therefore this study has enabled the reflexion on the professional teaching development, enlarging knowledge so that it results in innovation, (re)directing teaching through suitable methodologies and contents for the context of a rural school.